THE INFLUENCE OF A COMBINATION OF VIRTUAL REALITY ON THE INTERNET AT EVERGRANDE REAL ESTATE GROUP - Tianyu Wang; Suwatana Tungsawat (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
In recent years, there has been a growing tendency among businesses to use virtual reality (VR) to display their assets and the products they sell. When dealing with real estate, this method is innovative and on the cutting edge of the industry. It makes it easier for potential buyers to see the house in a new light. Furthermore, it streamlines the process of creating an educated decision about whether or not to buy the property by providing additional information about it. This study aimed to investigate the influence of virtual reality and the internet on the real estate sector. The study used a quantitative approach where 400 shareholders from Evergrande responded to the survey. The study found that the combination of virtual reality (VR) technology and the internet has already caused a positive revolution in the real estate industry and will continue to do so in the foreseeable future. Therefore, real estate agents and brokers must be knowledgeable about this technology to fully benefit from it and provide their customers with the highest level of service possible.